Study in Laboratory of Aqueous Solutions Representing the Acidity of a Uranium Mine Under Decommissioning - Mariana de Oliveira Reis; Alexandre Batista de Almeida; Linda Ayouni-Derouiche; Arno Heeren de Oliveira; Ricardo Geraldo de Sousa; Adriana de Souza Medeiros Batista (Brazilian Journal of Radiation Sciences, 2024)
The mine decommissioning process is associated to the mitigation of environmental impacts and recovery of degraded areas during the useful life of the unit. In the case of uranium mining, aspects concerning environmental radioprotection are necessary, thus avoiding increased human exposure to radiation and undesirable effects on the ecosystem. In order to adequately treat impacted areas, the possible form of management for environmental remediation will depend on the conditions of the particular mine. In the case of the Caldas Decommissioning Unit (UDC), mine acidity is a relevant issue, and the control of chemical elements in order to maintain the parameters defined by legislation must be continuously observed. Aiming to study strategic elements for the treatment of acid drainage water in the Caldas region, simulated solutions prepared in the laboratory, composed of Fe, Al and Mn, were proposed. It was possible to prepare a mixed solution with a concentration of these elements close to that found in the UDC, and representative of the acidity condition of the mine. The removal of elements by adsorption was also evaluated separately and together, verifying the influence of ions on the process. It was observed that the adsorbent material (RT) has a high adsorption power for iron, the ability to also adsorb manganese in concentrations close to those found in UDC, being influenced by the high aluminum content, which reduces its removal efficiency due to previous saturation. However, even in this case, the effectiveness of RT in treating acidic drainage waters is still evident, which can be enhanced by the combination of treatment methods. The study presented is especially relevant due to the conduct of activities that are representative of a real solution, but carried out in a controlled and simplified environment.